1992
DOI: 10.1073/pnas.89.11.4801
|View full text |Cite
|
Sign up to set email alerts
|

Mass determination and estimation of subunit stoichiometry of the bacterial hook-basal body flagellar complex of Salmonella typhimurium by scanning transmission electron microscopy.

Abstract: The basal body, a part of the rotary motor of the bacterial flagellum, is a multiprotein assembly that consists of four rings (denoted M, S, P, and L) and an axial rod (denoted R). From analysis of scanning transmission electron microscopy images of hook-basal body preparations isolated from Salmonella typhimurium, we have determined the masses of the basal body and three of its subcomplexes. The mass of the basal body (i.e., the four rings and rod) is 4400 ± 490 kDa (mean ± SD; n = 54). The mass of the LPR su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 19 publications
1
42
0
Order By: Relevance
“…An upper limit for the number of flagella per cell could be estimated from the FlgE content, given 130 (Ϯ 10%) FlgE subunits per hook structure (8,28). This upper limit was 7 Ϯ 1, comparable to the number measured by electron microscopy for E. coli grown under similar conditions (13).…”
Section: Vol 178 1996mentioning
confidence: 78%
“…An upper limit for the number of flagella per cell could be estimated from the FlgE content, given 130 (Ϯ 10%) FlgE subunits per hook structure (8,28). This upper limit was 7 Ϯ 1, comparable to the number measured by electron microscopy for E. coli grown under similar conditions (13).…”
Section: Vol 178 1996mentioning
confidence: 78%
“…Based on the arguments advanced in that publication and the performance of the flagella of our hinge mutants, we have concluded that, at least under some conditions, motor switching behavior cannot be entirely accounted for by a simple two-state model. We have simplified our discussion by considering only conformational changes in the 26 FliG subunits (15,20,40) in the rotor. These events can be viewed as the output of the switching event.…”
Section: Vol 186 2004 Mutations Affecting the Interdomain Region Ofmentioning
confidence: 99%
“…It is the first substructure to be assembled and anchors the flagellum in the cytoplasmic membrane (17). Twenty-six FliF monomers assemble into this ring structure (9,40,43), forming a central pore where the integral membrane components of flagellar export are located (4,16,27). The MS ring also interacts with the axial extension, the rod, on the periplasmic side and with the C ring in the cytoplasm ( Fig.…”
mentioning
confidence: 99%